The Impact of Tai Po Exercises on Some Elements of Health Fitness for Women with Diabetics (Type 1) - Hammodi, Iftekhar; Saeed, Wasan (Journal of Physical Education, 2022)
Diabetes is a common disease in the moment. Doctors often are often advised to have physical activities yet, there is no continuity due to boredom from physical exercises of a classic nature. Researchers suggested to use a special type of exercise represented by Tai Po exercises by using the experimental approach for a subject of fitness participants, (6) participants with type one diabetes, they applied Tai Po exercises for a (13) weeks, The results showed a moral improvement in the variables under consideration of sugar, cumulative sugar, mass and body mass index, as well as the heart's health status.